Renoprotective Effect of Chrysanthemum coronarium L. Extract on Adenine-Induced Chronic Kidney Disease in Mice - Yi-Seul Kim; Ae-Sin Lee; Haeng-Jeon Hur; Sang-Hee Lee; Hyun-Jin Na; Mi-Jeong Sung (MDPI AG, 2023)
Chronic kidney disease (CKD) gradually leads to loss of renal function and is associated with inflammation and fibrosis. Chrysanthemum coronarium L., a leafy vegetable, possesses various beneficial properties, including anti-oxidative, anti-inflammatory, and antiproliferative effects. In this study, we investigated the renoprotective effect of Chrysanthemum coronarium L. extract (CC) on adenine (AD)-induced CKD in mice. CKD was induced by feeding mice with an AD diet (0.25% w/w) for 4 weeks. Changes in renal function, histopathology, inflammation, and renal interstitial fibrosis were analyzed. The adenine-fed mice were characterized by increased blood urea nitrogen, serum creatinine, and histological changes, including inflammation and fibrosis; however, these changes were significantly restored by treatment with CC. Additionally, CC inhibited the expression of the inflammatory markers, monocyte chemoattractant protein-1, interleukins-6 and -1β, intercellular adhesion molecule-1, and cyclooxygenase 2. Moreover, CC suppressed the expression of the fibrotic markers, type IV collagen, and fibronectin. Furthermore, CC attenuated the expression of profibrotic genes (tumor growth factor-β and α-smooth muscle actin) in AD-induced renal injury mice. Thus, our results suggest that CC has the potential to attenuate AD-induced renal injury and might offer a new option as a renoprotective agent or functional food supplement to manage CKD.